Investigating the amount of Soluble COD Removal from Wastewater Containing Olive Oil Using Electrocoagulation: A Study of Kinetic Models - Mina Ghahrchi; Amir Adibzadeh; Abbas Rezaee (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: The olive oil industry wastewater contains significant amounts of oil and this can cause serious problems if it is discharged into the wastewater treatment system, so the oil in the wastewater must be removed and seperated prior to any action. Therefore, the oil in the sewage should be removed and separated prior to taking any measure. There are several ways to remove oil. According to the above, in the present study, the efficiency of the electro coagulation process in reducing soluble COD synthetic wastewater containing olive oil was investigated. Methods: In this study, iron and galvanized electrodes were used. Firstly, the optimum values of current density, initial pH, and electrolyte concentration were determined. Thereafter, the effect of time variations on electrode corrosion, voltage, decreased COD concentration, and energy consumption was investigated. The kinetics of Grade 1, Grade 2, and WeberMorris were also investigated for two electrodes. Results: The maximum removal efficiency of soluble COD was obtained at 99% for iron and galvanized electrodes at a current density of 12.5 mA/cm 2, electrolyte concentration of 400 mg / l, initial pH 7, and reaction time. The electrical energy consumption in these conditions for these two electrodes was measured at 28.5 and 46.25 KWhr/m3, respectively. Finally, kinetics models, including pseudo-first-order, pseudo-second-order, and Weber Morris, were investigated for these two electrodes. The results revealed that the highest correlation coefficient for both electrodes was related to the pseudo-second-order model. Conclusion: Although galvanized electrode is more efficient in the reduction of soluble COD concentration, as compared to iron electrode, it consumes more electrical energy. Therefore, the type of electrode must be selected according to the purpose.